The Determination of Heat Energy Requirement for Greenhouses with Different Hardware under Climate Conditions Antalya - Abdullah Nafi Baytorun; Sait Üstün; Adil Akyüz; Ali Çaylı (Turkish Journal of Agriculture: Food Science and Technology)
In Mediterranean climate region, during certain times of the year the daily average temperature decreases under 12°C. In such conditions, greenhouse heating is essential to be able to get the high quality yield that is expected from greenhouses. The cost of heating varies from 20% to 60% of the total costs depending on the climate of the region, size, type and hardware of the greenhouse and type of plant grown in the greenhouse. The heat requirement in greenhouses is calculated based on the rudiments defined by DIN 4701 standards. However, the real temperature in greenhouses is higher than the outside temperatures used in calculations. For this reason, the heat requirement in greenhouses should be calculated by taking temperature increases that are caused by ventilation temperature and heat storage capability into consideration. In this study, the heat energy need of Antalya which is located in Mediterranean region is assessed according to its climate conditions. In the calculations, the different hardware structures are considered and the level of energy that can be saved is calculated. As a result of the calculations, depending on the month of the year, 12% to 29% difference is observed between energy requirement calculations based on the indoor temperature increases and energy requirement calculations based on outside temperature values.